Effects of Inactivated Bordetella pertussis on Phosphodiesterase in the Lung of Ovalbumin Sensitized and Challenged Rats - Wang, Ya-Juan; Song, Shun-De; Chen, Jun-Chun; Wang, Xue-Feng; Jiang, Ya-Li; Xie, Qiang-Min; Chen, Ji-Qiang; Li, Zi-Gang; Tang, Hui-Fang (Pulmonary Medicine, 2014)
This paper indicated that inactivated Bordetella pertussis (iBp) can enhance the lung airway hyperreactivity of the rats sensitized and challenged with OVA. The mechanisms were involved in the upregulation of cAMP-PDE activity and PDE4A, PDE4D, and PDE3 gene expression in the lungs. But only PDE4 activity was different between the OVA and OVA+iBp groups, and PDE4D expression was significantly increased in iBp rats alone. So, our data suggested that cosensitization with OVA and iBp affects lung airway reactivity by modulating the lung cAMP-PDE activity and PDE4D gene expression.